Predictive Power of Net Profit On Share Returns - Muhaheranwa Benjamin, Vincent Konadu Tawiah, (International Journal of Scientific Research and Management (IJSRM), 2015)
The major indicator that attracts a person to invest in a company is the performance of the firm. Various measures such as ROA, ROE, and Tobin’s Q have been tagged on performance. But the traditional and objective measure is the net profit of the company. Using purposive sampling of 25 companies from NIFTY, this paper has attempt to find out the relationship, cause and effect between companies net profit and stock return an investor obtains within an accounting year. To achieve this, both univarate and bivariate analysis were run on a balanced panel data from 2009-2013 accounting years of the sample companies. The results reveal that companies had experienced an increasing profit over the period but the biggest portion is retained since a change in net profit results to less than proportionate change in dividend per share. Sock returns fluctuates much without a fixed pattern. Capital gain accounts for 95% of the total stock returns which also fluctuates over the time. Although net profit has positive impact on stock returns, it is not significant relationship. Because capital gains which is the biggest part of stock returns is not significantly influence by annual net profit. Hence, it is concluded that reported annual net profit does not have predictive power on total stock returns